Keto cookbook - Abrams, Rami; Abrams, Vicky (--For dummies., 2023)
"Millions of people have already benefited from the low-carb ketogenic diet. They've lost weight, increased their energy levels, got their Type 2 diabetes under control, and so much more. And if you're looking for an easy and fun way to get started with keto, look no further than the Keto Cookbook For Dummies! In this book, you'll find 150 delicious keto recipes, from cheesy egg casserole to a keto-inspired berry cobbler. You'll also discover expert tips on meal planning and preventing common ailments with simple adjustments to your diet. You'll even learn how to use your Instant Pot and air fryer to make full-flavor, low-carb keto dishes. The book also shows you how to: Swap in tasty keto alternatives for unhealthy ingredients, Make keto snacks and appetizers that give you a huge, long-lasting energy boost when you need it most, Prepare yummy keto sauces and staples you can make ahead of time and freeze for easy meal-prep during the week."--Publisher marketing.